FADS1, a lipid metabolism-related diagnostic biomarker in KIRC - Tianmin Yang; Kai Sun; Fan Peng; Yuhu Hao; Qingjie Bai; Hanpu Yu; Qinghua Xia (Discover Oncology)
Abstract Background Kidney renal clear cell carcinoma (KIRC), the predominant subtype of renal cell carcinoma, poses significant health risks. The rapid progression and resistance to targeted therapies highlight the need for new tumor markers and therapeutic targets. FADS1, part of the fatty acid desaturase family, regulates fatty acid synthesis and participates in lipid metabolism. However, its role in KIRC is not well-studied. Methods The study utilized bioinformatics analysis through the TCGA database and other platforms to identify FADS1 expression levels in KIRC. Twenty pairs of KIRC clinical tissue samples were used for qPCR verification. Meanwhile, eight pairs of KIRC clinical tissue samples were used for Western blot verification. Conduct statistical evaluation, including Wilcoxon rank sum test and Kaplan–Meier analysis, to explore the correlation between FADS1 expression and clinical pathological features and immune infiltration. In addition, in vitro experiments were conducted to confirm the biological function of FADS1. Results The findings indicated that FADS1 is highly expressed in KIRC and contributes to tumor development. FADS1's role in lipid metabolism leads to lipid accumulation within tumor cells, which may influence the occurrence and progression of KIRC. TIMER analysis revealed a correlation between FADS1 expression and the infiltration levels of various immune cells, indicating its potential role in modulating immune characteristics. Conclusion FADS1 could serve as a prognostic biomarker associated with immunity in KIRC, highlighting its potential as a diagnostic and therapeutic target. The study underscores the importance of further research into FADS1's role in lipid metabolism and immune infiltration to develop effective therapeutic strategies.